Increasing Student’s Self-regulation in Excretory System Learning: A Development of Learning Materials through Moodle - Wibisono, Bagus Tito; Rusdi, R; Komala, Ratna (Biosfer: Jurnal Pendidikan Biologi, 2022)
In Biology learning, technology becomes a tool to facilitate 21st-century learning trends that are digitally oriented, distanced, internet-integrated learning materials, as well as being open and independent. This trend is a challenge because the results of a preliminary study at SMAN 37 Jakarta showed that 42.3% of students experienced a decline in their biology learning outcomes during the distance learning period, especially in the Excretory System chapter. Of these, 61.5% thought the decline was due to low self-regulation. This study aims to develop learning materials in the Excretory System through Moodle to increase students’ self-regulation. The method used is research and development with the Borg and Gall development model using the Moodle platform. The development of learning materials was validated by 5 experts on aspects of the material, learning materials, and language. The result is the scope of the material aspect is 90.4%, the learning material aspect is 90.8%, and the language aspect is 88%, all of which meet the very feasible criteria. The learning materials were tested on 30 respondents and obtained pre-test and post-test scores on self-regulation. The results were tested using the paired sample t-test showed a significance value (p) = 0.001< 0.05. This result illustrated that the use of Excretory System learning materials can increase students’ self-regulation.